2022
DOI: 10.1371/journal.pone.0267542
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of neighborhood and individual socioeconomic status on mortality among older adults: Evidence from cross-level interaction analyses

Abstract: Background The influence of community context and individual socioeconomic status on health is widely recognized. However, the dynamics of how the relationship of neighborhood context on health varies by individual socioeconomic status is less well understood. Objective To examine the relationship between neighborhood context and mortality among older adults and examine how the influence of neighborhood context on mortality differs by individual socioeconomic status, using two measures of income-level and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…In the present study, we observed significant mortality inequity by SES for older people, which were in line with these of past research [32][33][34][35][36]. To name a few examples, Bassuk et al demonstrated that higher SES, as measured by education, by household income, or by occupational prestige, was generally associated with lower mortality in four American community-dwelling populations aged 65 years or more [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we observed significant mortality inequity by SES for older people, which were in line with these of past research [32][33][34][35][36]. To name a few examples, Bassuk et al demonstrated that higher SES, as measured by education, by household income, or by occupational prestige, was generally associated with lower mortality in four American community-dwelling populations aged 65 years or more [32].…”
Section: Discussionsupporting
confidence: 92%
“…To name a few examples, Bassuk et al demonstrated that higher SES, as measured by education, by household income, or by occupational prestige, was generally associated with lower mortality in four American community-dwelling populations aged 65 years or more [32]. Using the data from the 2014 to 2015 Medicare Health Outcomes Survey, Kim revealed that mortality rates were significantly higher in lowincome elders or non-homeowners when compared to their respective opposites [33]. Similarly, in another study consisted of 11 European populations, Huisman et al found persisted socioeconomic inequity in mortality among older men and women, and the SES in this study was indicated by educational level or housing tenure [34].…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of the low-income and higher-income groups indicated that, similar to findings in other investigations, adults in the low-income group were more likely to be in poor health (Kim et al, 2022;Park et al, 2017), live alone (Li & Dalaker, 2022), and have problems with housing quality and affordability (Kwon & Jang, 2017;Lee et al, 2014) and concerns about neighborhood safety (Kowitt et al, 2020;Park et al, 2017). At the same time, regression analyses indicated that for both the low-income and higher-income groups, health was significantly related to housing quality, household size, and neighborhood safety, suggesting that housing is a health determinant that crosses income boundaries.…”
Section: Discussionsupporting
confidence: 81%
“… 57 60 Lower neighborhood socioeconomic status has been linked to increased mortality risk. 61 , 62 There is strong evidence in literature that moving from high-poverty to lower-poverty neighborhoods can have a positive long-term effect on mental and physical well-being. 63 Lower nSES also has been associated with decreased mental health and reduced cognitive function.…”
Section: Discussionmentioning
confidence: 99%